Szlachetni, odważni, dzicy? Obraz Waregów i Franków w oczach Bizantyńczyków w X-XI w. - Wierzbiński, Szymon (Vox Patrum, 2018)
During Xth and XIth century the Byzantine Empire was one of the strongest states in the Levant. In mentioned period the emperors undertook numerous military campaigns, both in order to expand the borders of the empire and restitute their authority on once lost lands. Due to its prestige and wealth the Empire was a favorable destination for foreigners, including mercenaries. As a result, in Byzantium one could meet warriors of a very diversified ethnic descent. The presence of numerous foreigners could not escape the attentions of Byzantines themselves, who in time formed a distinctive view concerning those newcomers. Among many mercenaries two managed to obtain extraordinary status and step out in the eyes of Byzantine citizens. The first group were the Varangians, who at the end of Xth century formed the famous emperor`s guard. The second group of mercenaries were warrior from the West, usually referred to as the Franks. The main aim of this paper is to examine the genesis of mentioned warriors in Byzantium and the roots of stereotypes attached to them.